Identification of the Role of Stakeholders in Sustainable City Forests, Case Study of Beringin Medan City Forest, North Sumatra, Indonesia - Marpaung, Sutan Sahala Muda; Has, Dini Hardiani; Lubis, Dita Anggriani; Marpaung, Jihan Ulayya (Universitas Panji Sakti, 2024)
Management of forest cities becomes an essential strategy in strengthening environmental and social urban areas, particularly in facing the challenge of urbanization. This study aims to analyze stakeholders' roles, contributions, and strategies to increase synergy in the management of Medan Beringin City Forest. The MACTOR analysis method is used to understand the interaction between stakeholders and the factors influencing them. The results show that the involvement of various parties, including government regions, institutions, self-subsistent society, local community, and private sector, is essential in sustainable city management. City Government and Environment and Forestry Service's key roles in collaboration with other institutions are also seeded. Recommendation strategies can strengthen the effectiveness of management of forest cities, not only in Medan but also in other cities facing similar challenges.